Determination of the Fingerprint Chromatogram of Sanhuang Tablet by HPLC - Liu, Yan; Bi, Huimin; You, Fuying; Hu, Junping; Chai, Xingquan; Du, Yi (Asian Journal of Chemistry, 2012)
The establishment of fingerprint of Sanhuang tablets by HPLC offers an effective way for the quality control of Chinese patent medicine and its production. The chromatographic conditions are as follows: the column for the VP ODS C18 (4.6 mm × 150 mm, 5 μm), temperature is 30 ºC, a flow rate of 1.0 mL/min, detection at 280 nm, with methanol and 0.2 % aqueous solution of phosphate acid for mobile phase gradient elution. The results showed that 19 peaks were indicated on the HPLC fingerprint of Sanhuang tablet. According to the computer software-assisted analysis of similarity, the similarity of 10 batches of Sanhuang tablet was not lower than 0.98. The method was simple and reliable.